Negotiating Custom and Islamic Law: Reconstructing the Pisuke Tradition in Sasak Marriage through Symbolic Capital and Maqāṣid System Theory - Abal Yazid Abastommi; Kholid Saifulloh (Cakrawala: Journal of Religious Studies and Global Society, 2026)
This study aims to explain how the basis for determining the pisuke customary marriage payment among the Sasak community of Lombok has shifted from aristocratic lineage (Aji Krame) to women's formal educational attainment, and to reconstruct its legal status through an integrated socio-legal framework. The urgency of this inquiry lies in the fact that pisuke, a customary payment made by the groom's family to the bride's family independently of the Islamic mahar, has increasingly inflated to levels that impose severe financial hardship (masyaqqah), drive ribawi debt, and delay marriage among Sasak youth, while prior studies remain largely descriptive-ethnographic and have not operationalised a systemic theory of Islamic law to explain this shift. Using a qualitative legal-ethnographic design, data were collected in Kilang Village, East Lombok, through in-depth interviews with six purposively and snowball-sampled informants, participant observation, and documentation study, analysed thematically following Miles and Huberman's interactive model, and interpreted through Pierre Bourdieu's theory of symbolic capital and Jasser Auda's Maqasid System Theory. The findings show that women's academic credentials have become a vehicle for accumulating symbolic capital and status competition among families, shifting pisuke's legal status from 'urf sahih to 'urf fasid. The study concludes that this shift can be reversed through a novel conceptual model, Tradition-Negotiation-Moderation-Maslahah, which operationalises Auda's principles of openness and purposefulness to reconstruct pisuke as a flexible voluntary gift (hibah) rather than a rigid marital precondition.